HIV-infection in the arctic zone of the republic of Sakha (Yakutia): status, challenges and prospects - A. G. Zolotareva; S. S. Sleptsova; S. S. Sleptsov; T. E. Burtseva (Журнал инфектологии)
The stable increase in morbidity and mortality of the population of the Republic of Sakha (Yakutia) from causes related to HIV infection indicates an unfavorable epidemiological situation in the region. Especially it affects industrial areas and large settlements of Yakutia. In the near future, an increase in the number of HIV-infected patients in the republic is expected, which is alarming. The HIV epidemiological situation is aggravated by the unequal distribution within the region with extremal environmental conditions and underdeveloped transport infrastructure. All this makes it much more difficult to provide medical care to this category of people, some of whom later move outside the territory of the Republic.Aim: Improvement of effective preventive measures and organization of medical care in the Arctic regions of the Republic of Sakha (Yakutia) based on the analysis of morbidity and mortality from HIV infection.Materials and methods: The materials of official statistics of the Department of the Federal Service for Supervision of Consumer Rights Protection and Human Welfare in RS(Ya) and data from official governmental medical reports (forms № 61 and № 4) were used in the work.Results: The number of HIV-infected people on the territory of the Republic of Sakha (Yakutia), including in the Arctic regions, is growing in recent years. Thus, from 1998 to 2022, 77 new cases of HIV infection were detected in the Arctic regions, more than half of which (54.5%) were registered in the period from 2016 to 2022. The tendency of growth of the indigenous population affected by HIV infection, including in remote areas of the region, that dictates the need for mandatory HIV screening of all persons arriving for shift work both from neighboring countries and from other regions of the Russian Federation.Conclusion: Preventive measures, HIV testing and organization of medical care are the basis for effective fight against this disease, especially in remote Arctic regions of the Republic of Sakha (Yakutia).